Effects of carbon-based impurities on graphene growth. Issue 22 (25th May 2018) - Ge, Xiaoming; Zhang, Yanhui; Chen, Zhiying; Liang, Yijian; Hu, Shike; Sui, Yanping; Yu, Guanghui; Peng, Songang; Jin, Zhi; Liu, Xinyu
Abstract : The effects of carbon-based impurities on the nucleation and growth of graphene are clarified. Abstract : In this paper, we studied the growth of graphene on an untreated Cu substrate and further studied the effect of carbon-based impurities on the nucleation of graphene in different growth environments. It is found that the impurities on the surface of the Cu substrate easily lead to damage of the graphene, and the impurities do not always promote nucleation as previously reported, but inhibit nucleation in a high etching environment. Finally, based on experimental results, a model of nucleation and growth of graphene around impurities is presented.